Innovative environment of a modern higher education institution as an object of competitiveness - Shtefan, L (Problems of Engineer-Pedagogical Education, 2019)
Market relations, in which education is also involved, require that they comply with the relevant demands of existence. One of these is the competitiveness of higher education institutions in the labor market. To bring the level of educational services to the level of modern requirements, a higher education institution must have an appropriate innovative environment. The article analyzes the terminological research field through the definition of the essence of the concepts «competitiveness of a higher education institution» and «innovative environment». From a position of a systematic approach, external and internal factors affecting the competitiveness of the innovative environment of an educational institution are considered and specified. Among the external factors are the means of state influence, which determine the rules of the entity in the national and world markets; characteristics of the market itself; activity of state and non-state institutions; activities of political parties, movements, blocs that shape socio-political circumstances in the country. Internal factors are determined by marketing, financial and economic, and personnel potential; advertising effectiveness; material and technical support, and other opportunities that form the strategic potential of an institution. The matrix of comparative analysis of the main indicators of its activity is considered as one of the ways to assess the competitiveness of the innovation environment. The way implies that these indicators are identified by means of the expert assessment method and critically analyzed in accordance with the environment of educational institutions that compete in the market of educational services among themselves. At the same time, the positions on which higher education institutions might lag behind are clearly defined. A parallel is drawn between the competitiveness of higher education institutions and the quality of professional training of specialists. The assumption is made that in order to meet quality management requirements one should use the triple helix model. The concept of the triple helix model is the close interaction of the university, government and business. The application of this approach will help higher education institutions to resolve the issue of creating a competitive innovation environment.